Legal Consensus as to Embargo Claims; an Investigative Study - Jayalath, Chandana (International Journal of Scientific Research and Management (IJSRM), 2018)
Certain political sanctions have been recently imposed against Qatar by Bahrain, Egypt, Saudi Arabia and the United Arab Emirates. Given the fact that Qatar is very busy constructing a number of projects in preparation for the FIFA World Cup in 2022, it’s unsurprising that the Quantity Surveyors have had some requests for advice from contractors whose operations in Qatar have been affected by the sanctions and who are looking for a means of claiming extension of time and/or damages. Equitable principles codified in the Qatar Civil Law include the requirement for parties to a contract to conduct themselves "consistent with the dictates of good faith" and an implied duty of the employer to cooperate with its contractors and not to delay or prevent their contract performance. Furthermore, where a contractor has suffered excessive losses arising from exceptional events the contractor may be able to raise an exceptional event's argument pursuant to Article 171 of the Qatar Civil Law, and if successful, the approach is to reduce the contractor's burdensome obligation to a reasonable limit after balancing the interests of the parties. This paper is to explore the legal consensus pertaining the embargo in Qatar using civil codified law provisions, standard forms of contracts for public works and the author’s firsthand experience in drafting and review of claims on embargo.